Identification of a novel autoantigen eukaryotic initiation factor 3 associated with polymyositis. (17th September 2019) - Betteridge, Zoe; Chinoy, Hector; Vencovsky, Jiri; Winer, John; Putchakayala, Kiran; Ho, Pauline; Lundberg, Ingrid; Danko, Katalin; Cooper, Robert; McHugh, Neil
Abstract: Objectives: To describe the prevalence and clinical associations of autoantibodies to a novel autoantigen, eukaryotic initiation factor 3 (eIF3), detected in idiopathic inflammatory myositis. Methods: Sera or plasma from 678 PM patients were analysed for autoantigen specificity by radio-labelled protein immunoprecipitation (IPP). Samples immunoprecipitating the same novel autoantigens were further analysed by indirect immunofluorescence and IPP using pre-depleted cell extracts. The autoantigen was identified through a combination of IPP and MALDI-TOF mass spectrometry, and confirmed using commercial antibodies and IPP-western blots. Additional samples from patients with DM (668), DM-overlap (80), PM-overlap (191), systemic sclerosis (150), systemic lupus erythematosus (200), Sjogren's syndrome (40), rheumatoid arthritis (50) and healthy controls (150) were serotyped by IPP as disease or healthy controls. Results: IPP revealed a novel pattern in three PM patients (0.44%) that was not found in disease-specific or healthy control sera. Indirect immunofluorescence demonstrated a fine cytoplasmic speckled pattern for all positive patients. Mass spectrometry analysis of the protein complex identified the target autoantigen as eIF3, a cytoplasmic complex with a role in the initiation of translation. Findings were confirmed by IPP-Western blotting. The three anti-eIF3-positive patients had no history of malignancy or interstitial lung disease, and had a favourable response to treatment. Conclusion: We report a novel autoantibody in 0.44% of PM patients directed against a cytoplasmic complex of proteins identified as eIF3. Although our findings need further confirmation, anti-eIF3 appears to correlate with a good prognosis and a favourable response to treatment.